2016
DOI: 10.2147/ijwh.s120027
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of polycystic ovary syndrome in young reproductive females in Qatar

Abstract: This was a prospective cross-sectional study in which 126 female students between the ages of 18 and 30 years were evaluated for the frequency of polycystic ovary syndrome (PCOS) through clinical interview, questionnaire, and anthropometric measurements. The diagnostic criteria of the US National Institutes of Health criteria were used. Menstrual irregularities (MI) were identified, and clinical hyperandrogenism was evaluated by self-assessment of hirsutism using modified Ferriman–Gallwey score. Blood analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
6
23
1
Order By: Relevance
“…Acne was present in 26% of Iranian women, 31% of Qatari women, and a prevalence rate of 50–80% was reported in Turkey and Palestine. 34 , 35 , 41 , 42 While persistent occurrence of patches of thick dark skin was reported by 13.5% of students in our study, 23% of Indian adolescents had also reported the same in a previous study. 43 These results indicated the presence of a highly PCOS predisposed cohort in our study population that was confirmed when 13.4% of students self-reported being detected with PCOS by a physician, with 3.5% also taking medication for the same.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Acne was present in 26% of Iranian women, 31% of Qatari women, and a prevalence rate of 50–80% was reported in Turkey and Palestine. 34 , 35 , 41 , 42 While persistent occurrence of patches of thick dark skin was reported by 13.5% of students in our study, 23% of Indian adolescents had also reported the same in a previous study. 43 These results indicated the presence of a highly PCOS predisposed cohort in our study population that was confirmed when 13.4% of students self-reported being detected with PCOS by a physician, with 3.5% also taking medication for the same.…”
Section: Discussionsupporting
confidence: 69%
“…PCOS is linked to menstrual disorders like poly and oligomenorrhea (observed in 28% of Iranian women, 31% of Qatari women, and 19% of Indian adolescents) and other symptoms such as hirsutism, acne, and elevated androgen levels. 34 , 35 Our participants also reported irregularities such as poly menorrhea (30.7%) and oligomenorrhea (3.5%), and there was a positive association of detection of PCOS and duration of menstrual cycle ( P =0.02). This differs from other studies that have reported higher incidence of oligomenorrhea compared to polymenorrhea.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A small study of Qatari women estimated that the prevalence of PCOS was 18.3% and in a larger Qatari cohort was found to be 12.1% using NIH guidelines 13 , 14 , which could reflect a much higher incidence of prediabetes and T2D in these patients compared to a Caucasian population. This current study has used the national Qatar Biobank (QBB) to try and establish the incidence of T2D and prediabetes in PCOS Qatari women, with the hypothesis that if the prevalence of PCOS is increased in this population, then the prevalence of IGT and T2DM will also be increased proportionately.…”
Section: Introductionmentioning
confidence: 94%
“…Among these symptoms, menstrual irregularity is the most representative symptom of PCOS. Although we excluded subjects with previously diagnosed PCOS and obese subjects during enrollment, subjects with undiagnosed PCOS may not have been fully excluded, since PCOS is a common but often undiagnosed condition [37]. Therefore, many female patients with undiagnosed PCOS visit dermatological clinics to treat their acne.…”
Section: Discussionmentioning
confidence: 99%